An incoherent scatter radar study of the midnight temperature maximum that occurred at Arecibo during a sudden stratospheric warming event in January 2010. Issue 6 (2nd June 2016) - Gong, Yun; Zhou, Qihou; Zhang, Shaodong; Aponte, Nestor; Sulzer, Michael
Abstract: We present an analysis of the thermospheric midnight temperature maximum, a large increment of temperature around midnight. The analysis is based on data collected from the Arecibo incoherent scatter radar during 14–21 January 2010. The experiment overlaps with a major sudden stratospheric warming (SSW) event which commenced on 18 January 2010. Throughout the observation, the ion temperature exhibited moderate increase around postmidnight during 14–17 January, while it showed more intense increment during 18–21 January. In particular, on 20 January, the amplitude of the midnight temperature maximum (MTM) is 310 K, which is seldom seen at Arecibo. During the SSW, the meridional wind reverses toward the pole just before the commencement of the MTM. Then, the poleward wind and the ion temperature maximize almost at the same time. The variation of meridional wind and the MTM are consistent with the Whole Atmosphere Model (WAM) studies, which suggested that the variation is due to effects from an upward propagating terdiurnal tide. On the nights of 18–19 January, the MTM showed clear phase variation at the heights of 265, 303, and 342 km. A strong terdiurnal tide has been observed during the SSW and it is likely generated from low atmosphere and propagating upward. Our results provide direct observational evidence that the propagating upward terdiurnal tide plays an important role in causing the MTM, which supports the WAM simulations. Key Points: Prominent MTM with amplitude of 310 K has been observed at Arecibo The MTM is suggested to be generated by an upward propagating terdiurnal tide associated with the SSW Provide direct observation evidence to support the model studies